Inclusive Labor Market and Participation of Person with Disabilities: Case Study in Indonesia, Denmark, France, and Ireland - Suwitanty, Ananda Putri Pratama; Setyari, Ni Putu Wiwin (Universitas Muhammadiyah Ponorogo, 2024)
An inclusive labor market for persons with disabilities is one of the priority issues discussed in the G20, especially in the Employment Working Group (EWG) field. Typically, the number of individuals with disabilities participating in the labor market is lower than that of their non-disabled counterparts, mainly due to the company’s reluctance to hire disabled workers. This study aims to investigate the impact of disability on participation in the inclusive labor market. This research uses panel data from four countries - Indonesia, Denmark, France, and Ireland - spanning the years 2016 to 2021, sourced from the International Labor Organization (ILO). The variables used to determine the factors that influence the participation of individuals with disabilities in the labor market are their educational level, the number of disabled individuals in rural areas and their average income. By using the Fixed Effect Model, it is known that people with disabilities who have received education and the number of people with disabilities living in urban areas have a positive and significant effect on the participation of people with disabilities in the labor market. Meanwhile, the average income of people with disabilities has a negative and insignificant effect on the participation of people with disabilities in the labor market. Efforts to increase the participation of people with disabilities in the labor market are important as welfare reform, indicators of the success of inclusive development and poverty alleviation among groups of people with disabilities.